PERAN PEMERINTAH TERHADAP LANJUT USIA PADA PANTI SOSIAL TRESNA WERDHA SINTA RANGKANG DI KOTA PALANGKA RAYA - Rahmaniar, Rahmaniar; Sukmana, Enriko Tedja; wulandari, Sri (AL-QARDH, 2016)
Elderly was someone who was at the age of 60 years and older with conditions of reduced function of the health, social and economic.The condition was often the elderly had problems in terms of neglected or abandoned by families and communities. Overcoming the problems of the elderly in neglected or abandoned, the government has been providing social welfare institution of Tresna Werdha Sinta Rangkang for the elderly. Social welfare institution was a residence for the elderly who did not had a place to stay with the purpose of empowering the neglected elderly and abandoned. However, such observations can be in social welfare institution have a policy that only receives elderly healthy and independent. In fact, that should be more in need were elderly who were not in these circumstances in order to be empowered in this social institution.Then, with the issue of this study discusses the role of government to the elderly at social welfare institution of tresna Werdha Sinta rangkang in the city of Palangkaraya. The formulation of the problem, namely: (1) What is the role of government on the economy of the elderly in the city of Palangkaraya. (2) How is the role of government to the elderly in Social Welfare Institution Tresna Werdha Sinta rangkang.This study, a field research using qualitative descriptive approach.The object of this study is the role of government in the city of Palangka Raya and the research subject is the section head elderly Provincial and head of the Social Welfare Institution of Tresna Werdha Sinta Rangkang in the city of Palangkaraya. Methods of data collection by observation, interview and documentation.